Hubungan Inisiasi Menyusui Dini Dengan Kelancaran Pengeluaran ASIPada Ibu Post Partum KF 1 Di PMB Tuti Khairina Kabupaten Serdang Bedagai Tahun 2023 - Misdawati Misdawati; Nopalina Suyanti Damanik (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Service quality can be measured by comparing perceptions between the expected service and the service received and felt by the patient. Patient satisfaction is the level of patient feelings after comparing with his expectations. If a patient is satisfied with the value provided by a product or service, it is very likely that they will become a customer for a long time. The aim of this research is to analyze the relationship between service quality in the registration section and patient satisfaction for pregnant women at the Highlands Assistant Health Center, Highlands District, Binjai City in 2023. The type of research used in this study is analytical with a cross-sectional approach with the research sampling technique being non-probability sampling. or non-random sampling was carried out at PMB Tuti Khairina, Serdang Bedagai Regency with a sample of 32 KF 1 post partum mothers from February to May 2023. The results of the chi-square test obtained a p value = 0.001 (p <0.05). This means that there is The Relationship between Early Initiation and the Smooth Expenditure of Breast Milk in Post Partum KF 1 Mothers in PMB Tuti Khairina Serdang Bedagai Regency in 2023